2014
DOI: 10.1371/journal.pone.0096927
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sea Water Prevents Balloon Angioplasty-Induced Hyperplasia through MMP-2: An In Vitro and In Vivo Study

Abstract: Major facts about the development of restenosis include vascular smooth muscle cells (VSMCs) proliferation and migration. A previous study showed that in vitro treatment with magnesium chloride has the potential to affect the proliferation and migration of VSMCs. Magnesium is the major element in deep sea water (DSW) and is a biologically active mineral. It is unclear whether DSW intake can prevent abnormal proliferation and migration of VSMCs as well as balloon angioplasty-induced neointimal hyperplasia. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Numerous studies have confirmed that DSW has pharmacological effects, including protecting the cardiovascular system (12,13), improving metabolic processes (14,15), anti-osteoporosis properties (16), treating atopic dermatitis skin lesions (17), accelerating recovery from physical fatigue (18), providing intestinal protection against duodenal ulcers (9) and inhibiting the metastatic potential of human breast cancer cell lines (19 Although DSW has already been studied for its alleviating fatigue effect in Wistar rats, the beneficial effects isolated in that study were only attributed to the minerals of DSW (20). In addition, the mechanism behind the beneficial effect has not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that DSW has pharmacological effects, including protecting the cardiovascular system (12,13), improving metabolic processes (14,15), anti-osteoporosis properties (16), treating atopic dermatitis skin lesions (17), accelerating recovery from physical fatigue (18), providing intestinal protection against duodenal ulcers (9) and inhibiting the metastatic potential of human breast cancer cell lines (19 Although DSW has already been studied for its alleviating fatigue effect in Wistar rats, the beneficial effects isolated in that study were only attributed to the minerals of DSW (20). In addition, the mechanism behind the beneficial effect has not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…DSW moves continually in a cycle throughout the ocean, and accounts for about 90 % of the whole sea volume (Miyamura et al 2004). DSW has been used in therapies for the treatment and prevention of various diseases, such as hyperlipidemia, artherosclerosis, hypertension, and dermatitis (Yoshioka et al 2003;Hataguchi et al 2005;Li et al 2014). Compared with surface sea water, DSW is cleaner and more hygienic, with abundance of minerals including magnesium (Mg (Katsuda et al 2008;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DSW has been used in therapies for the treatment and prevention of various diseases, such as hyperlipidemia, artherosclerosis, hypertension, and dermatitis (Yoshioka et al 2003;Hataguchi et al 2005;Li et al 2014). Compared with surface sea water, DSW is cleaner and more hygienic, with abundance of minerals including magnesium (Mg (Katsuda et al 2008;Li et al 2014). Minerals are essential factors for the health and appropriate development of humans (Ayaz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of minerals, such as calcium (Ca), magnesium (Mg), vanadium (V), zinc (Zn), and potassium (K). Many studies have shown that DSW can be effectively used to treat diabetes, obesity, hyperlipidemia, and hypertension (Sheu et al 2013;Ha et al 2014b;Li et al 2014;Yang et al 2014). Mg supplementation improves myocardial metabolism and inhibits myocardial cell death.…”
Section: Introductionmentioning
confidence: 99%